Transformation of Mustahik into Muzakki Through Independent Entrepreneurship: A Study on the Financial Management of MSME in the Z-Chicken Program - Sudirman; Alimuddin; Darwis Said; Madrianah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The purpose of this study is to explore the practice of mustahik financial management as MSE actors in the Z-Chicken productive zakat program organized by the National Amil Zakat Agency (Baznas) of Pangkep Regency, and assess the role of mustahik assistance to become muzakki. The background of this research is that the capital assistance program and production training that have been given to mustahik to become independent MSE actors still experience obstacles in their implementation. Namely, the inability of MSE actors to separate business and personal finances, as well as the lack of maximum assistance programs carried out by program organizers that have an impact on the sustainability of the beneficiaries' businesses. This research uses a qualitative approach of case studies, where the perpetrators are mustahik as the beneficiaries of the program and the Pangkep Regency Baznas as the program manager and companion. Data were obtained through interviews, observations, FGDs, and documentation, then analyzed with Miles and Huberman's interactive models, and tested for validity using triangulation of sources and methods. The results show that financial management practices are still weak, and turnover is often considered a profit without a separation between capital and margin. The main inhibiting factors include household financial literacy, low financial literacy, lack of record-keeping habits, and a culture of dependence on aid. Baznas' role in mentoring is more focused on technical, production, and digital marketing aspects, while the financial literacy aspect has not been optimal. Theoretically, this research strengthens the theory of microfinance and financial capabilities in the context of productive zakat, while practically providing recommendations for Baznas to integrate financial literacy training and sustainable mentoring into social economic empowerment programs.